The Influence of Javanese Speaking Civility in Families to Form Child Character in The 21st Century - Rachma Mutiara Dewi; Zahrotun Nafi'; Rahmah Karuniawati; Ratna Hidayah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
Education in the family is the first education experienced by a child after being born in the world. The family is the main environment forming the character of children. In this 21st century, children are required to have good moral character. Parents should be able to transmit good etiquette to their children. The main task of parents is not only transferring knowledge, but also transferring values to children. The process of transferring knowledge carried out by parents will succeed if done with the right and right principles. Parents as good educators are able to accustom children to speak good, polite, and gentle words. One of them by way of habituating Javanese manners. The purpose of this study is to study 1) The custom of Javanese manners; 2) children's character in the 21st century; 3) Family education; 4) the formation of character in the family through the Javanese language of manners. The result of this goal is the habit of using polite language in a family environment which influences the character formation of children in the 21st century.